Strategi Pengelolaan Sumber Daya Manusia di Lembaga Kesejahteraan Masjid Rahmatan Lil Alamin Al-Zaytun Indramayu - R. Aziz Mayardhi Basoeky; Ahmad Asrof Fitri; Meity Suryandari (Tabsyir: Jurnal Dakwah dan Sosial Humaniora, 2024)
Factors such as leadership behavior, employee compensation, and related policies significantly impact employee engagement in achieving organizational performance. Case studies from large and medium-sized companies in Indonesia indicate that achieving shared goals requires balancing performance targets at every individual level. This study analyzes human resource management (HRM) at the Rahmatan Lil Alamin Mosque Welfare Institution, Al-Zaytun Indramayu, and formulates HRM strategies using SWOT analysis.The findings show that HRM at the Rahmatan Lil Alamin Mosque Welfare Institution, Al-Zaytun, is implemented through two main approaches: motivation and soft skill development. The motivational approach aligns with fulfilling employees' physiological needs, while the soft skill approach addresses the need for security, appreciation, love, and self-actualization. The SWOT analysis reveals that the institution's internal strengths include standardized systems and procedures, well-managed human resources, and clear job descriptions for each role. Identified weaknesses are the absence of job analysis as a foundation for HR planning and recurring disciplinary violations. Externally, opportunities include utilizing e-commerce and implementing minimum service standards, while threats arise from individuals or parties who oppose the institution's existence.